Comparative Study of Rhodamine B degradation by Tio2 nanoparticles synthesized from titanium sec butoxide and its chloroacetato derivatves - Ambreen, S.; Pandey, N. D.; Pandey, A. (Cellular and Molecular Biology, 2017)
TiO2 has been well recognized as a proficient photocatalyst. TiO2 nanoparticles have been synthesized from titanium sec butoxide (1) and its monochloroacetate derived compounds. The modifications of Ti(OsBu)4 with monochloroacetic acid in 1:1 and 1:2 molar ratios afforded Ti(OsBu)3(OOCCH2Cl) (2) and Ti(OsBu)2(OOCCH2Cl)2 (3), respectively. The use of monochloroacetic acid as a modifier allows the control of both the degree of condensation and oligomerization of the precursor. The cross linking of the gel and connectivity of the molecular building blocks are lowered in these heteroleptic alkoxides which results in the formation of gels instead of crystalline precipitate. This modification of the precursors leads to the generation of new building blocks which significantly affect the properties of the resulting TiO2. TiO2 powders were prepared via sol-gel method from these precursors and calcined at 400°C and 600°C for 4 h. Phase and morphology of the prepared metal oxide nanoparticles were studied. XRD patterns showed TiO2 in anatase phase. After coating with the surfactant trioctyl phosphinoxide (TOPO), TiO2 particles were dispersed in chloroform to study the particle size and distribution. The optical properties were studied by UV-VIS drs. The photocatalytic activity was studied over the degradation of Rhodamine B under UV radiation.